PENAMBATAN MOLEKUL SENYAWA AKTIF CURCUMA XANTHORRHIZA ROXB KANDIDAT ANTI KANKER KOLOREKTAL TERHADAP RESEPTOR LYMPHOCYTE-SPECIFIC PROTEIN TYROSINE KINASE - Sativa, Nasywa Oryza; Putri, Adelia Ofira; Natasya, Zaskiya; Rislia, Rana Atikah; Ulfa, Lutfiyana; Karima, Miska Aulia; Balqis, Selvi; Saputro, Anjar Hermadi; Auli, Winni Nur (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2024)
Background: Temulawak (Curcuma xanthorrhiza Roxb) contains essential oils and curcuminoid compounds which have anti-cancer activity. Temulawak (Curcuma xanthorrhiza Roxb) can increase colorectal cancer chemotherapy agents against Lck receptors on colon epithelial cells. Purpose(s): The aim of this research is to identify active compounds that have the potential to act as colorectal anticancer contained in Temulawak (Curcuma xanthorrhiza Roxb) against Lck receptors through in silico studies using molecular docking methods. Methods: This study was carried out of molecular docking using software AutoDock Tools-1.5.6., Lipinski predictions with LigandScout, and visualitation using Biovia Discovery Studio 2021 Client. Results: Xanthorrizol has hydrogen bonds with the same amino acid residues as native ligand and reference compound, namely GLU317 and MET319. The results of the molecular binding energy of the native ligand are -10.12 kcal/mol. Conclusion: Based on research results, the xanthorrizol compound has the best potential to be a colorectal anticancer candidate and qualified of Lipinski's rules so it is safe to be administered orally.